2022
DOI: 10.3390/ijerph19031665
|View full text |Cite
|
Sign up to set email alerts
|

Natural Bioactive Compounds in the Management of Oral Diseases in Nephropathic Patients

Abstract: Among the chronic non-communicable degenerative diseases (CDNCDs), chronic kidney disease (CKD) represents a global public health problem. Recent studies demonstrate a mutual cause–effect relationship between CKD and oral diseases, in which the presence of one induces the onset and faster progression of the other. In particular, the oral cavity alterations more frequent in CKD patients are: chronic periodontitis diseases, bone lesions, oral infections, and oral cancer lesions. Currently, a standardized therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 114 publications
(135 reference statements)
1
5
0
Order By: Relevance
“…In this study, as already demonstrated in previous studies by our research group, the intake of products based on fruit, vegetables, EVOO, and natural extracts rich in antioxidant compounds belonging to the class of polyphenols, showed an improvement in the clinical status of CKD patients [20][21][22][23]25]. The obtained results confirm the positive effect of APA on body composition and on clinical status, alone or in synergy with functional bars, resulting in an adjuvant tool to counteract related-CKD comorbidities [11,82].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, as already demonstrated in previous studies by our research group, the intake of products based on fruit, vegetables, EVOO, and natural extracts rich in antioxidant compounds belonging to the class of polyphenols, showed an improvement in the clinical status of CKD patients [20][21][22][23]25]. The obtained results confirm the positive effect of APA on body composition and on clinical status, alone or in synergy with functional bars, resulting in an adjuvant tool to counteract related-CKD comorbidities [11,82].…”
Section: Discussionsupporting
confidence: 89%
“…Directly applied to the oral malignant lesion, the UBA-loaded mucoadhesive oral films could exert a topical anticancer effect, reducing the progression of oral squamous cell carcinoma. This formulation could also help through other mechanisms [ 113 ]. Because OSCC decreases immune defense, the oral cavity becomes more susceptible to bacterial and fungal infections.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by Noce et al demonstrated that CKD progression is also related to oral dysbiosis [ 12 , 170 , 171 ]. In particular, three oral pathological conditions (oral infections, periodontitis and uremic stomatitis) may induce and exacerbate systemic chronic inflammation [ 172 ].…”
Section: The Possible Link Between Oral Dysbiosis and Gut Dysbiosis A...mentioning
confidence: 99%